P- waves reflected from the "20" discontinuity" beneath the Mediterranean region - B. FEDERICO; A BOTTARI (Annals of Geophysics, 1975)
The observed travel-times of the P-waves for twenty
shallow, intermediate, and deep earthquakes, with epicenters in the Mediterranean
area, are used in order to analyze some characteristics of the
upper mantle.
A first- order discontinuity, identifiable as the "20° discontinuity",
is found at a depth of 505 ± 16 km in the area underneath the Mediterranean
basin. The velocity contrast is equal to 12% (above T'= 8.9 km/sec;
below V= 9.97 km/sec).
Assuming that this discontinuity gives rise to reflected P-waves (PdP),
the travel times of these waves are calculated for various hypocentral depths.
The observation of impulses identified as PdP on the seismograms of
Messina supports this hypothesis.
This result and its implications are discussed in the contest of the
conclusions of various authors who locate a P-wave velocity-discontinuity
at different depths between 400 and 580 km.
Finally, particular emphasis is given to the regional character of the
analyzed structures in question.